Geothermal barriers, policies and economics in Chile – Lessons for the Andes. (November 2015) - Sanchez-Alfaro, Pablo; Sielfeld, Gerd; Campen, Bart Van; Dobson, Patrick; Fuentes, Víctor; Reed, Andy; Palma-Behnke, Rodrigo; Morata, Diego
Abstract: The Andes is the largest undeveloped geothermal region in the world. The Chilean case is the most puzzling because the country is largely dependent on imported fuels causing, among other issues, high energy prices and energy dependency. But even though it has large quantities of geothermal resources which have been explored since the 1920s, no geothermal power plant has been constructed yet. The barriers for geothermal development in Chile have not been studied in detail and limited information is available about the real economic feasibility of geothermal power generation and whether effective incentives are needed for its development. In this study we present an integrated analysis of geoscientific, economic, historical and regulatory aspects of geothermal development in Chile based on the compilation of new and previously published data. Through a survey of key participants from government institutions, industry and academia we identified the main perceived advantages, barriers, and efficient incentives. The absence of clear medium-to-long term energy policies and a lack of government incentives for companies to overcome financial risk are perceived as the main barriers. Additionally, we calculated the estimated average Levelized Costs of Energy (LCoE) of geothermal electricity generation using different scenarios to illustrate the potential impact of possible government policies. At present conditions and without incentives we estimated a base case geothermal LCoE in Chile which would be "near competitive" compared to the average contract prices. Further analysis would be needed to estimate the effect of different policy incentives more rigorously. Finally, we propose some guidelines for geothermal stakeholders to encourage geothermal power development; these might prove useful to other Andean and developing countries as well.